Preparação e caracterização de materiais híbridos de pani(adbs)/zno e sua aplicação em adsorção/fotodegradação - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
Polyaniline (PANI) is a polymer that stands out from the group of so-called Intrinsically Conducting Polymers (ICPs), due to its good environmental stability and easiness to obtain, generating the interest of researches focused on its possible applications, such as photocatalysis and hybrid preparations. One of the strategies to improve the polyaniline's processability it is doping it with functionalized protonic acids with organic groups, as is the case of dodecylbenzenesulfonic acid (DBSA), which improves its solubility in nonpolar solvents. Zinc oxide (ZnO), compound with several applications (inks industry, medicine, cosmetics industry and pharmaceutical industry) also has photocatalytic properties. The association between PANI and semiconductor compounds, such as ZnO, has been proposed to study its properties, among them the photocatalytic potential of this joint compounds called hybrid materials. The aim of this study was to synthesize DBSA doped polyaniline and prepare their hybrids with ZnO, obtaining PANI(DBSA)/ZnO, both by conventional methods, as using sonication in order to verify their applications in photobleaching of organic compounds. The synthesized samples were characterized by electrical conductivity measurement techniques, IR spectroscopy, thermogravimetry, transmission electron microscopy (TEM) and X-ray diffraction, indicating the presence of polyaniline in the samples, as well as those with the best features of interest. Analysis showed that, in some samples, the methylene blue removal capacity in the presence of UV light ranged from 18% to 75%, in average, in 1 hour of irradiation. In adsorption tests and photodegradation, it was found that the time of sample sonication, temperature of the reaction medium and the system condition (or rest stirring) directly influenced the dye removal. Under studied conditions, it was found that the hybrid PANI(DBSA)/ZnO showed no photocatalytic properties, but those synthesized by sonication have significant adsorbent potential and can be used for this purpose.
Keywords: Polianilina; Óxido de zinco; Fotodegradação; Sonicação; Materiais híbridos; Polyaniline; Zinc oxide; Photodegradation; Sonication; Hybrid materials; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA